Vagal indigestion in mini-cattle1 - Ferreira, Lucas V.O. [UNESP]; Lourenço, Maria L.G. [UNESP]; Takahira, Regina K. [UNESP]; Alonso, Juliana M. [UNESP]; Oliveira-Filho, José P. [UNESP]; Borges, Alexandre S. [UNESP]; Chiacchio, Simone B. [UNESP]; Amorim, Rogério M. [UNESP] (FapUNIFESP (SciELO), 2023)
Ferreira L.V.O., Lourenço M.L.G., Takahira R.K., Alonso J.M., Oliveira-Filho J.P., Borges A.S., Chiacchio S.B. & Amorim R.M. 2023. Vagal indigestion in mini-cattle. Pesquisa Veterinária Brasileira 43:e07240, 2023. Departamento de Clínica Veterinária, Faculdade de Medicina e Zootecnia, Universidade Estadual Paulista “Júlio de Mesquita Filho”, Rua Prof. Doutor Walter Mauricio Correa s/n, Cx. Postal 560, Botucatu, SP 18618-681, Brazil. E-mail: rogerio.amorim@unesp.br Vagal indigestion (VI) is a digestive disorder characterized by the dysfunction of the vagus nerve. This disorder leads to changes in forestomach motility. The causes of VI are varied. Failure to transport digestive contents may occur due to mechanical obstruction or a neurogenic origin. There are few reports in the literature regarding this disease in mini-cattle. These cattle seem to be predisposed to the development of VI. The aim of the present study was to analyze the epidemiological, clinical, laboratory, and electrocardiographic aspects of mini-cattle diagnosed with VI. The medical records of nine mini-cattle diagnosed with VI were retrospectively reviewed. Mini-cattle were referred to the Large Animal Hospital in Botucatu, Brazil, from 2002 to 2021. It was observed that VI affected young mini-cattle. The predominant clinical manifestations were intermittent gas ruminoreticular tympanism with increased volume in the left paralumbar fossa and increased volume in the right ventral region (apple/pear aspect), hypomotility in ruminal auscultation and the presence of pasty stools. The mean heart rate of the animals was 75 beats per minute. In one case, bradycardia was observed by electrocardiogram and Holter monitor system. In this case, the predominance of parasympathetic activity of the autonomic nervous system was observed. The main hematological findings were leukocytosis and lymphocytosis. The therapeutic approach included ruminal fistulation and the implantation of a permanent rumen cannula. All animals undergoing the procedure were discharged with daily care instructions.
Keywords: Abdominal distension; mini-cattle; tympany; vagal indigestion; vagus nerve